PERLINDUNGAN HUKUM KEPADA ANAK DI BAWAH UMUR TERHADAP TINDAK PIDANA PENCABULAN (TINJAUAN KASUS No.2795/Pid.Sus/2017 PN Medan) - Juniko Andreas Sihombing (Ilmu Hukum Prima (IHP), 2019)
Legal protection given to children as victims of sexual abuse by obscene perpetrators includes: rehabilitation efforts, given to children as victims of criminal acts of sexual abuse by providing a psychological rehabilitation effort for the child, so that the child can return to normal in the community. And the factors that cause the crime of sexual abuse against minors in this case are internal factors such as religious, family, psychiatric, psychological, external factors in the form of environmental factors. And where in the judge's consideration of criminal acts of molestation to children brought to age (review decision number: 2795 / PID.SUS / 2017 / PN.Medan) in accordance with the evidence in this case, namely witness statements, letters, and statements of defendants that are mutually relevant, so that the panel of judges gained the conviction that the defendant had committed an offense against the underage child, namely with article 81 paragraph (1) in conjunction with article 6D of Law No. 35 of the year concerning child protection. Therefore the author expects the participation of the police to conduct intensive supervision of cases of criminal acts of molestation to minors. And to parents and the surrounding community to pay more attention to and improve supervision of children, and get attention from parents.And to the government in order to be able to carry out tighter supervision of the development of the internet at this time.